Cardiogenic headache - Cvetković, Ana (Medical Research, 2023)
Cardiogenic headache has a small incidence, and unrecognized can prolong the time to diagnose a life-threatening condition such as an acute coronary event. According to its clinical presentation, it can refer to a migraine headache. Even in the absence of clinically and laboratory evident signs, the diagnosis of cardiogenic migraine should be kept in mind because sometimes it is the only symptom of a threatening coronary event. The choice of treatment depends on a correctly established diagnosis. The reckless inclusion of vasoconstrictors as a standard therapeutic modality of migraine in a patient with a cardiogenic headache could worsen ischemia and endanger the patient’s life. Solving an acute coronary event conservatively, with percutaneous coronary interventions or coronary "bypass," also eliminates cardiogenic headache.